2018
DOI: 10.2147/dmso.s154304
|View full text |Cite
|
Sign up to set email alerts
|

Decreased health-related quality of life in patients with diabetic foot problems

Abstract: PurposeThe aim of this study was to investigate health-related quality of life (HRQoL) in patients with diabetic foot problems and compare the HRQoL between diabetic patients with: 1) diabetic foot problems (DF), including diabetic foot ulcer (DFU) or amputation (AMPU); 2) other diabetic complications (COM), such as diabetic retinopathy (DR), end-stage renal disease (ESRD), or coronary artery disease (CAD); and 3) no diabetic complication (CON).Patients and methodsA total of 254 diabetic patients were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 12 publications
8
40
0
4
Order By: Relevance
“…5 Other research has also indicated moderate or decreased satisfaction with the QoL related to health. 19,20 However, based on our findings and the lack of research reporting on the impact of the QoL related to foot health in patients with type II and type I diabetes, the findings of our study confirmed that people with type II diabetes presented with a specific foot impact on the QoL dimension related to general foot health compared with patients who suffered from type I diabetes. Thus, these findings showed the importance of diabetic foot and podiatric care to prevent foot problems and amputations and improve the QoL and autonomy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…5 Other research has also indicated moderate or decreased satisfaction with the QoL related to health. 19,20 However, based on our findings and the lack of research reporting on the impact of the QoL related to foot health in patients with type II and type I diabetes, the findings of our study confirmed that people with type II diabetes presented with a specific foot impact on the QoL dimension related to general foot health compared with patients who suffered from type I diabetes. Thus, these findings showed the importance of diabetic foot and podiatric care to prevent foot problems and amputations and improve the QoL and autonomy.…”
Section: Discussionsupporting
confidence: 77%
“…Diabetic foot problems have been recognised as an important public health problem, as stated by Al‐Rubeaan et al, who analysed 62.681 patients with diabetic foot and risk factors, reporting 1285 patients (62.05%) with foot ulcers and 677 patients (32.20%) with foot gangrene, which increased with the age, duration of the diabetes, and male gender . Other research has also indicated moderate or decreased satisfaction with the QoL related to health …”
Section: Discussionmentioning
confidence: 96%
“…Previous studies on DFU and the heavy burden it poses on Saudi Arabia (where its incidence is in the 11.4-29.7% range) have shown that HRQOL is unfavorably affected by it [ 6 , 16 , 17 ]. Unfortunately, there is a paucity of data on the detrimental effects of foot ulcers on the HRQOL of diabetes patients in Saudi Arabia, which has inspired the current study.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Diabetic foot ulcer affects not only the quality of life and physiological welfare but also premortal events and following major leg amputations due to the ulcer, mortality ranges from 24.6% within 5 years and 45.4% within 10 years. [17][18][19][20][21] It is also estimated that 24.4% of the total health care expenditure among the diabetic population is related to foot complications. 22 The pooled worldwide prevalence of DFU in people diagnosed with diabetes mellitus is 6.3%, of which most (13%) is in North America, 7.2% in Africa and the lowest (3%) in Europe.…”
Section: Introductionmentioning
confidence: 99%